Nanostructured Solar Cells - Hans Agren (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
This book covers major important aspects of nanostructured solar cells of varying types. From fundamental physicochemical investigations to technological advances, and from single junction solar cells (silicon solar cell, dye sensitized solar cell, quantum dots sensitized solar cell, and small molecule organic solar cell) to tandem multi-junction solar cells, all aspects are included and discussed to advance the use of nanotechnology to improve the performance of solar cells with reduced fabrication costs. Most recent studies of nanostructured solar cells have been integrated in this book, allowing readers to quickly follow recent developments in this area.